2005
DOI: 10.4049/jimmunol.175.6.3554
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Induction of Lung and Airway Allergy in the Offspring of IFN-γ-Treated Mother Mice

Abstract: Recent studies have highlighted the influence of fetal/maternal interactions on the development of asthma. Because IFN-γ reduces Th2-mediated allergic responses, we assessed its capacity to modulate asthma in the offspring when injected into mothers during pregnancy. IFN-γ was injected in CD1 female mice on day 6.5 of gestation. Immediately after birth, male newborns were housed in cages with interchanged mothers: the offspring from IFN-γ-treated mothers were breastfed by normal mothers (IFN/nor), and those fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 49 publications
(31 reference statements)
0
19
1
4
Order By: Relevance
“…Most unique to OVA-CFA-primed mice was the predominance of OVA-specific IFN-␥ production by T cells following sensitization, the virtual absence of eosinophil recruitment to the airways following aerosol challenge and high levels of OVA-specific IgG2a in serum. It has been shown that treatment of pregnant CD1 mice with rIFN-␥ (100 IU at E6.5) protects offspring from developing severe allergic airway disease upon sensitization and aerosol challenge (73). An analogous correlate in humans is the demonstration that maternal stable work (i.e., exposure to environments rich in microbial products) during pregnancy is more protective against development of atopy in children than maternal stable work during lactation (32).…”
Section: Discussionmentioning
confidence: 88%
“…Most unique to OVA-CFA-primed mice was the predominance of OVA-specific IFN-␥ production by T cells following sensitization, the virtual absence of eosinophil recruitment to the airways following aerosol challenge and high levels of OVA-specific IgG2a in serum. It has been shown that treatment of pregnant CD1 mice with rIFN-␥ (100 IU at E6.5) protects offspring from developing severe allergic airway disease upon sensitization and aerosol challenge (73). An analogous correlate in humans is the demonstration that maternal stable work (i.e., exposure to environments rich in microbial products) during pregnancy is more protective against development of atopy in children than maternal stable work during lactation (32).…”
Section: Discussionmentioning
confidence: 88%
“…4 This concept is further supported by the fact that injection of IFN-␥ at high doses during pregnancy prevents the offspring susceptibility to allergy. 29 Increased levels of IL-13 were found both in pregnant and virgin recipient mice, suggesting a direct link between IL-13 overproduction and the adoptive transfer of allergen-specific T cells. Moreover, IL-13 levels were higher than any other cytokine assayed in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, recipient females received no further stimulus that could interfere with conception or fetal development. Other studies of maternal influence on asthma risk have made significant progress using pregnant female mice injected with exogenous cytokines, 29 sensitized to allergens, 11 or allergen-challenged during pregnancy. 12 However, in these experiments the exogenous stimuli may theoretically reach the fetus and directly induce responses attributed to the modulation of maternal immunity, which confounds interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…A transmissão perinatal é a principal via de infecção pelo HIV na população infantil, sendo que na ausência de procedimento profilático (administração de HAART) a estimativa da ocorrência da infecção é de 25,5%, sendo que destes, 65% dos casos ocorrem no trabalho de parto (MS, 2005). Com a profilaxia antiretroviral, a TMC foi reduzida para menos que 1% em alguns países (Mandelbrot et al, 2001).…”
Section: Infectam (Unaids 2008)unclassified
“…Apesar do número de crianças infectadas ser significante, o Brasil realizou um dos grandes avanço no que diz respeito à diminuição de casos de TMC (MS, 2005). Entretanto este tipo de transmissão é ainda agravante em regiões da África e Ásia.…”
Section: Introductionunclassified